An investigation of term creation in Northern Sotho - Mojapelo, Welhelmina Mamahlobega (My University, 2018)
This mini dissertation investigate term creation in Northern Sotho/ Sepedi as a language. The research design for this study was exploratory because the researcher managed to determine the research design and data collected from the participants. The qualitative methodology was applied in this study to find in-depth knowledge on the investigation. The two samplings namely: random and purposive were used to select twenty participants such as teachers, lecturers, language practitioners, lexicographers and registered third year students of Northern Sotho at University of Limpopo. The study investigate various strategies in term creation namely: transliteration, semantic transfer, borrowing, paraphrasing, and many more. It was clear from the participants that transliteration and paraphrasing are mostly used in term creation. It is recommended that terms should be harvested by specialised individuals in order to perform term creation.
Thesis (M. A. (Translation Studies and Linguistics)) -- University of Limpopo, 2018
Keywords: Northern Sotho terms; Term creation; Northern Sotho language - terms and phraces; Terms and phraces